Analisa Level Kinerja Struktur Pada Bangunan 12 Lantai Dengan Metode Pushover - Zuher, M. Hasbi; Sidiq, Zairah Nabila; Nasution, Ade Prayoga; Masrilayanti, Masrilayanti; Sunaryati, Jati (Jurnal Talenta Sipil, 2024)
There have been many earthquakes in Indonesia, especially West Sumatra. There was a fairly large earthquake, one of which was in 2009 with a magnitude of 7.6 on the Richter scale centered in Padang Pariaman, causing damage to vulnerable structures and loss of life. Therefore, evaluating the seismic vulnerability of buildings before an earthquake occurs is an important step in preventing damage to buildings and loss of life. In this study, a pushover analysis was carried out to determine the level of structural performance. The method used is a 12-storey building where both the existing building and its detailed properties are known, modeled using the Software Structural Analysis Program (SAP2000) Version 23. From the analysis results, the structure of the 12-storey building will experience the first yield point when given the 3rd pushover load, both at in the X-direction and Y-direction and the building structure will collapse when given the 10th pushover load in the X-direction and the 8th in the Y-direction. The performance level of the 12-story building structure is included in the Damage Control (DO) category level for the X-X direction, which means the transition between Immediate Occupancy (IO) and Life Safety (LS). Meanwhile, in the Y-Y direction, the structure is included in the Immediate Occupancy (IO) category level. Thus, in this case the building is still able to withstand the burden of the earthquake that occurred, the building can also be used again when it has received the earthquake load and the risk of human casualties is relatively small.